Employees Perception on Quality Circle Program Effectiveness in Five Selected Malaysian Companies - Abo-Alhol, Tariq R. A. (2004)
The purpose of this study is to examine the effectiveness of participation in Quality Circles (QCs). The study looked at major factors affecting QCs effectiveness, which are namely; employees involvement, adequacy of training, leadership, employee perception, purpose of setting up QCs, number of projects implemented, management support, job satisfaction, commitment and willingness to expand effort, and intent to quit.